Avaliação da Interação dos Antirretrovirais Lamivudina, Efavirenz eTenofovir e seus excipientes - Elionai Cassiana de Lima Gomes (2015)
Efavirenz (EFV), lamivudine (3TC) and tenofovir disoproxil fumarate (TDF) are among the most worldwide antiretrovirals for AIDS treatment. In this work, Solid-State Nuclear Magnetic Resonance (ssNMR), Fourier-transform Infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and thermooptical analysis (TOA) were used to study possible interactions between these drugs, aiming the development of a fixed-dose combination (e.g., two or more active pharmacological products in the same formulation) of ARVs (antiretrovirals). DSC and TOA showed significant shifts of the melting temperatures of drugs in the mixtures EFZ-3TC and EFZ-TDF, suggesting an interaction between them. Slight changes were observed in the TDF-3TC mixture, which may be due to solubilization of 3TC after melting of TDF (which presents lower melting point than 3TC). The FTIR spectra showed no change due to overlapping bands. ssNMR analysis showed no significant changes in chemical shift values () of the mixtures when compared to the pure drugs, except for the EFZ-TDF mixture, which showed a significant shift of the signals of the carbon nuclei near groups able to participate of hydrogen interactions. These results suggest that interaction occurs only between EFZ-TDF mixture, since the ssNMR did not confirm the interactions of EFZ-3TC mixture suggested by DSC and TOA results. Regarding the excipients, 3TC presented evidence of incompatibility with lactose spray dried. EFZ presented evidence of incompatibility with the excipients lactose spray dried , opadry and PVP- K30. TDF showed evidence of incompatibility with the magnesium stearate and lactose spray dried. It can be concluded that the production of a formulation containing the three drugs is possible, provided that strategies are employed to minimize contact between TDF and EFZ, to prevent a possible incompatibility between them.